Water quality assessment based on biological and chemical analysis as a parameter for development of fresh water fishery in Lubuk Karet River of Banyuasin District - Carli Junicef Vratama; Siti Masreah Bernas; Mohamad Amin (Research Centre of Inorganic Materials and Complexs, 2018)
Lubuk Karet River is a river that surrounded by swamps with various kinds of plants and grasses. The Lubuk Karet River has the potential for the development of aquaculture which can be the business part of Lubuk Karet village community. This research was aimed to conduct an assessment effort in order to measure the capability of Lubuk Karet River for any aquaculture activities. The method used in this study is purposive sampling by conducting water quality assessment through biological and chemical parameters to support the development in that region. The results of this test can be a benchmark of fish species that can be cultivated in the Lubuk Karet River. The results of the chemical and biological parameters showed that the lowest DO content at station 2 was 3.11 mg/L and the highest BOD content at station 1 was 4.7 mg/L, the highest at station 1 was 606 mg/L, the highest TSS content 50 mg/L, the highest nitrate content at station 1 was 6,54 mg/L, the highest phosphate content at station 2 was 0.098 mg/L, the highest COD content at station 2 was 5,61 mg/L, Salinity was 0, the highest content at station 2 was 9,71 mg/L and the lowest pH value at station 5 was 2.96. From these results, it can be concluded that for further utilization for aquatic culture, some treatments must be conducted.